Cellular protein breakdown and systemic inflammation are unaffected by pulmonary rehabilitation in COPD - Bolton, Charlotte E (BMJ Group, 2007)
BACKGROUND: Pulmonary rehabilitation can improve the functional capacity, but has a variable effect on the low fat‐free mass (FFM) in patients with chronic obstructive pulmonary disease. HYPOTHESIS: Pulmonary rehabilitation would not affect catabolic drives such as systemic inflammation and also protein breakdown. METHODS: Patients (n = 40) were studied at the start of an 8‐week in‐patient pulmonary rehabilitation programme, at the end of the programme and 4 weeks later. FFM and functional capacity (quadriceps strength, handgrip strength and peak workload) were assessed. Pseudouridine (PSU) urinary excretion (cellular protein breakdown) and inflammatory status were determined. Healthy participants had a single baseline assessment (n = 18). RESULTS: PSU, (IL)‐6 and soluble tumour necrosis factor (sTNF)α R75 were increased in patients compared with healthy participants, whereas FFM and functional capacity were reduced (all p<0.01). PSU was inversely related to both FFM and skeletal muscle function. FFM and functional parameters increased with rehabilitation, but PSU and inflammatory status were unaffected. The gain in FFM was lost 4 weeks after the completion of rehabilitation (p<0.01). CONCLUSION: The anabolic effect of pulmonary rehabilitation improved FFM, but it did not reverse the increased protein breakdown or systemic inflammation. Thus, on cessation of pulmonary rehabilitation the FFM gains were lost owing to a loss of anabolic drive.